Effects of Housing System, Swimming Pool and Slaughter Age on Duck Performance, Carcass and Meat Characteristics - Erisir, Z.; Poyraz, O.; Onbasilar, E. E.; Erdem, E.; Oksuztepe, G. A. (Medwell Online, 2009)
The aim of this study was to determine the effects of different housing systems, swimming pool and slaughter age on performance, carcass and meat characteristics of ducks. A total of 420 (212 male, 208 female) one day old ducklings (Star 52-Grimaud Freres) were obtained from a commercial hatchery. The ducklings were randomly divided into four treatment groups; two Intensive Systems (IS) (one without pool and the other with swimming pool) and two intensive systems with outside activity (IOS) (one with swimming pool and the other without pool). Each group included 105 (53 male and 52 female) ducklings. European Efficiency Factor (EEF), feed efficiency and livability rate were affected by the housing system, swimming pool and age. Housing system and slaughter age significantly affected the slaughter weight and cold carcass yield. Breast, legs and wings percentages were significantly affected by slaughter age. PH(24), cooking loss, ash, protein and lipid contents of leg muscle were significantly altered by age. PH(24), ash, protein and lipid contents increased while, the cooking loss decreased with age. Housing system had no effect on the carcass chemical composition. From the point of EEF the market age of Pekin ducks at 6 weeks is more beneficial due to the better feed efficiency, lower feed intake and lower feed cost. Open sided area and swimming pool enhanced the EEF.
Keywords: Duck; housing system; carcass; meat characteristics; swimming pool; slaughter age